Kyrgyz Republic Public Expenditure Review Policy Notes : Intergovernmental Fiscal Relations - World Bank (Washington, DC, 2014)
Intergovernmental fiscal relations have advanced over the last decade in the Kyrgyz Republic. Since the previous public expenditure review in 2004, the government of the Kyrgyz Republic has developed a number of policy changes in the area of intergovernmental fiscal relations. These policy changes helped the country to introduce a more transparent and equitable system of local government financing. Still, effective decentralization continues to face challenges. A set of policy recommendations for the government to consider are designed to clarify the role of local government and provide better incentives for improved service delivery. These are based on a review of the four pillars of intergovernmental fiscal relations in Kyrgyz Republic: (i) the expenditure assignment (of who does what); (ii) revenue assignment (with what resources) assignment; (iii) the system of transfers; and (iv) borrowing. In this context, the report is structured as follows: section one gives executive summary. Section two provides a brief description of the institutional context in terms of the structure of government and the elements of political and administrative decentralization. Section three analyzes the delineation of expenditure responsibilities among government tiers. Section four analyzes revenue sources assigned to each tier of government. Section five focuses on the system of intergovernmental transfers. Section six examines subnational public investments and borrowing. In each of these sections main issues and problems are identified in the current system and the desired directions for reform are pointed out.